PENGEMBANGAN MEDIA PAPAN BATANG NAPIER TERHADAP PEMAHAMAN PERKALIAN DUA ANGKA DI SDN KAMALAKA - Hilma Galby; Nazmie Nabilah; Salsabila Anatasya Aisyah; Anggi Rahmani (Universitas Teknokrat Indonesia, 2026)
This study aims to develop a Napier's bone learning medium for integer multiplication for fifth-grade students at SDN Kamalaka and to determine the feasibility and effectiveness of this medium in supporting the learning process. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The developed media was validated by subject matter experts and media experts, then tested on 21 fifth-grade students. The validation results showed that the Napier's Bead board media was very feasible to use, with an increase in the material validation score from 88.2% to 91.7% and an increase in the media validation score from 89% to 95.3% after revision. The students' post-test results also showed an increase in their understanding of the concept of two-digit multiplication, accompanied by high enthusiasm and motivation during the learning process.